Improving the Electrochemical Performance of Pouch Cell Electric Double-Layer Capacitors by Integrating Graphene Nanoplates into Activated Carbon - Shaker, Majid; Sadeghi Ghazvini, Ali Asghar; Feng, Shuang; Cao, Weiqi; Meng, Xiaomin; Ge, Qi; Riahifar, Reza (Energy Technology, 2021)
Herein, activated carbon (AC) is composited with multiple weight ratios of graphene nanoplates through a facile and scalable technique, including sonicating and vacuum mixing in a slurry to fabricate pouch cell electric double-layer capacitors (EDLCs). Among the fabricated devices, the EDLC made of 2 wt% graphene/AC composite demonstrated the best electrochemical performance by enhancing the specific capacitance of AC EDLC from 27.3 to 39.3 F g−1 at 0.05 A g−1 current density. Moreover, the addition of graphene to AC leads to a more ideal capacitive behavior, reduction of charge transfer resistance (Rct) of the AC EDLC from 2.04 Ω to below 0.05 Ω, and the decrease of the ohmic drop at a current density of 2 A g−1 from 18.7% to 5.7%. 2 wt% graphene was considered as the optimum amount to be added to AC to increase the specific capacitance on average by 40% and improve the capacitance retention to 97% after 1000 cycles at 1 A g−1. Furthermore, the fabricated EDLC based on the optimum ratio of graphene to AC possessed satisfactory energy densities of 13.7 and 8.3 Wh kg−1 at 50 and 2000 W kg−1 power densities, respectively.
CRIS-Team Scopus Importer:2021-11-19
Keywords: activated carbon; electric double-layer capacitors; graphene; nanocomposites; pouch cells